2002
DOI: 10.2134/jeq2002.0690
|View full text |Cite
|
Sign up to set email alerts
|

Microcosm Wetlands for Wastewater Treatment with Different Hydraulic Loading Rates and Macrophytes

Abstract: Constructed wetlands (CW) usually require large land areas for treating wastewater. This study evaluated the feasibility of applying CW with less land requirement by operating a group of microcosm wetlands at a hydraulic retention time (HRT) of less than 4 d in southern Taiwan. An artificial wastewater, simulating municipal wastewater containing 200 mg L(-1) of chemical oxygen demand (COD), 20 mg L(-1) of NH4+-N (AN), and 20 mg L(-1) of PO4(3-)-P (OP), was the inflow source. Three emergent plants [reed, Phragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Emergent vegetation may reduce nutrient concentrations in surface water even more strongly, as has been demonstrated particularly in wetlands used for wastewater treatment (Tanner et al, 1999;Verhoeven & Meuleman, 1999;Meuleman et al, 2002). Several studies have demonstrated that the retention time of water is very important for the amount of nutrients stored in the vegetation (Jing et al, 2002;Busnardo et al, 1992).…”
Section: Factors Influencing Nutrient Retentionmentioning
confidence: 98%
“…Emergent vegetation may reduce nutrient concentrations in surface water even more strongly, as has been demonstrated particularly in wetlands used for wastewater treatment (Tanner et al, 1999;Verhoeven & Meuleman, 1999;Meuleman et al, 2002). Several studies have demonstrated that the retention time of water is very important for the amount of nutrients stored in the vegetation (Jing et al, 2002;Busnardo et al, 1992).…”
Section: Factors Influencing Nutrient Retentionmentioning
confidence: 98%
“…The ranking of species is not definitive in the literature. Plant species does not make a difference in many studies (Bachand and Horne, 2000;Jing et al, 2002). Typha latifolia out-performed in some species comparison (Coleman et al, 2001), while in others its efficiency may decreased during winter (Allen et al, 2002).…”
Section: Species Differentiationmentioning
confidence: 99%
“…cold hardiness) are biological attributes for HSSFCW application (IWA, 2000). There are some comparison studies, for different set of species, but they are not always conclusive (Bachand and Horne, 2000;Jing et al, 2002). Also, species applicability can change with latitude and local climate.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, the Phayao and Koh Phi Phi provinces used 140-180 m 2 and 750 m 2 as horizontal flow wetland system for treatment of different wastewaters [14]. The wetland systems for wastewater treatment normally require large land area [15]. Other authors have evaluated the feasibility of applying constructed wetland in limited land areas in Taiwan, and the results showed that using plant cultivation in wetland areas could remove nutrients much better than without using it [15].…”
Section: Application Of Eco-techniques For Wastewater Treatmentmentioning
confidence: 99%
“…The wetland systems for wastewater treatment normally require large land area [15]. Other authors have evaluated the feasibility of applying constructed wetland in limited land areas in Taiwan, and the results showed that using plant cultivation in wetland areas could remove nutrients much better than without using it [15]. A horizontal surface flow constructed wetland system using sand and reed has been implemented in Can Tho University, Vietnam, for the purpose of evaluating treatment capability and velocity in the tropical condition [16].…”
Section: Application Of Eco-techniques For Wastewater Treatmentmentioning
confidence: 99%